An expert support system to aid tribal environmental personnel in water quality assessments - Johnson, Stephen W., author; Smith, Freeman M., advisor; Waltz, James P., advisor; Loftis, Jim C., committee member; Ward, Robert C., committee member (Colorado State University. Libraries, 2000)
The U.S. Environmental Protection Agency (EPA) encourages Indian Tribes to develop the capability to assess and report on the quality of water resources on Reservations. A Tribal water quality assessment report under Clean Water Act Section 305(b) provides a means for Tribal environmental decision makers to manage water quality in a meaningful manner and to guide protection, restoration, and assessment efforts. One of the major obstacles to Tribal production of305(b) reports is the lack of technical transfer of information to Tribal environmental personnel regarding appropriate water quality monitoring, assessment, and reporting methods. The expert support system (ESS) developed for this dissertation is the first of its kind and is designed to eliminate the technical transfer obstacle for tribal 305(b) reporting. The ESS operates on a Windows 95 platform. The executable ESS and Users Manual reside on the internet at www.naein.com/NativeAmerican/crit/index.html.
Keywords: hydrology; environmental science; Native American studies